CoS2 Nanoparticles Embedded in Covalent Organic Polymers as Efficient Electrocatalyst for Oxygen Evolution Reaction with Ultralow Overpotential. Issue 20 (27th August 2021) - Ma, Qian; Liao, Rongfeng; Lu, Yuheng; Liu, Shaohong; Tang, Youchen; Zhu, Youlong; Wu, Dingcai
Abstract: Cobalt disulfide (CoS2 ) has been explored as attractive electrocatalyst for oxygen evolution reaction (OER). However, bulk CoS2 sheets have limited catalytic activity due to low exposure of active sites. Herein, through an in‐situ vulcanization approach, CoS2 nanoparticles are embedded into bipyridine‐containing covalent organic polymer (BP‐COP). The as‐prepared nanocomposite CoS2 @BP‐COP exhibits high catalytic activity toward OER with an ultra‐low overpotential of 270 mV (vs. RHE) at a current density of 10 mA cm −2, a small Tafel slope of 36 mV dec −1, and an excellent durability for 24 h without decay. The surface of CoS2 is partially converted into CoOOH to form CoS2 /CoOOH as active sites under OER conditions. CoS2 @BP‐COP displays superior OER catalytic activity to CoS2 nanosheets and commercially available RuO2 under the same conditions. The outstanding OER performance activity of CoS2 @BP‐COP could be attributed to the uniform and small particle sizes of CoS2 /CoOOH distributed in BP‐COP. Abstract : CoS2 with uniform and small particle size embedded in a covalent organic polymer (CoS2 @BP‐COP) has been successfully synthesized by an in‐situ vulcanization approach. CoS2 @BP‐COP possesses much more electrocatalytic active sites and notable enhancement of OER activity in comparison with bulk CoS2 nanosheets, boosting OER performances with ultra‐low overpotential (270 mV vs. RHE) and long‐term stability.